2005
DOI: 10.1021/jf0516179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbonated Fatty Methyl Esters Using Supercritical Carbon Dioxide

Abstract: The two-step syntheses of the cyclic carbonates carbonated methyl oleate (CMO) and carbonated methyl linoleate (CML) are reported. First, synthesis of epoxides through well-precedented chemical reactions of unsaturated fatty methyl esters with hydrogen peroxide and formic acid was accomplished. Next, a carbonation reaction with a simple tetrabutylammonium bromide catalyst was performed, allowing the direct incorporation of carbon dioxide into the oleochemical. These syntheses avoid the use of the environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 28 publications
6
64
0
Order By: Relevance
“…Fatty ester carbonates have the physical and chemical properties useful for preparing different valuable chemicals for many applications [132][133][134][135]. There are two main benefits of the conversion of fatty acid derivatives/epoxidized oils into cyclic carbonates.…”
Section: Conversion Of the Olefinic Functional Groups Into Cyclic Carmentioning
confidence: 99%
See 3 more Smart Citations
“…Fatty ester carbonates have the physical and chemical properties useful for preparing different valuable chemicals for many applications [132][133][134][135]. There are two main benefits of the conversion of fatty acid derivatives/epoxidized oils into cyclic carbonates.…”
Section: Conversion Of the Olefinic Functional Groups Into Cyclic Carmentioning
confidence: 99%
“…Tamami et al reported on the synthesis of carbonated soybean oil from epoxidized soybean oil at an atmospheric CO 2 pressure using tetra-n-butylammonium bromide ([Bu 4 N]Br) as a catalyst [137]. An improved protocol for the synthesis of carbonated oleo compounds was described by Doll et al [133]. They have synthesized carbonated methyl oleate and carbonated methyl linoleate from epoxy derivatives of fatty esters using supercritical carbon dioxide directly with a catalytic amount of tetrabutylammonium bromide.…”
Section: Conversion Of the Olefinic Functional Groups Into Cyclic Carmentioning
confidence: 99%
See 2 more Smart Citations
“…This scheme was applied to epoxidized soybean oil and shown to convert the oxirane to the carbonate with carbon dioxide at atmospheric pressures in the presence of tetrabutylammonium bromide 12,13) . Similarly, it was shown that epoxidized methyl oleate could be carbonated with supercritical carbon dioxide 14) . The availability of epoxidized vegetable oils and the corresponding epoxidized esters suggests a ready supply of renewable substrates for the production of long chain cyclic carbonates.…”
Section: Introductionmentioning
confidence: 97%